SOME characteristic properties of analytical method of magnetic control of ferroimpurities in various primary and technological media - Sandulyak, Anna A.; Sandulyak, Alexander V.; Bulut, Hasan; Baskonus, Haci Mehmet; Polismakova, Maria N.; Sandulyak, Darya A. (E D P Sciences, 2016)
The paper demonstrates that when defining the content of ferroimpurities in the analyzed media by magnetic control based on measuring the ferroimpurities masses m, which are extracted from the media sample step-by-step, it is crucial to define a functional view of the obtained dependence m on the operation order number n. It allows receiving additional forecast data m by extrapolating this dependence. With corresponding calculations being done, it enables determining the sought total mass of ferroimpurities (including their residual mass). We consider alternate solutions of practical tasks which yield magnetic control results in case of linear and piecewise-linear views (in semi-logarithmic coordinates) of the control mass-operational characteristics.
20th International Conference on Circuits, Systems, Communications and Computers (CSCC) -- JUL 14-17, 2016 -- Corfu, GREECE